Interaction of Meso-tetra-(4N-allylpyridyl) porphyrin and its Cu-, Co- and Zn- containing derivatives with DNA - V. G. Barkhudaryan; G. V. Ananyan (ՀՀ ԳԱԱ հրատ.)
The influence of water soluble cationic meso-tetra-(4N-allylpyridyl) porphyrin (H2TAlPyP4) and its metal complexes with Cu-, Co- and Zn- on hydrodynamic and spectral behaviour of ct-DNA solutions has been studied by viscometry and UV-VIS spectrophotometry methods. The results obtained were compared with the results of previously conducted similar studies on meso-tetra-(3N-allylpyridyl) porphyrin (H2TAlPyP3). Մածուցիկաչափության և սպեկտրոֆոտոմետրիայի մեթոդներով հետազոտվել է ջրալուծ կատիոնային մեզո-տետրա-(4N-ալլիլպիրիդիլ) պորֆիրինի (H2TAlPyP4) և Cu-ի, Co-ի և Zn-ի հետ նրա համալիրների ազդեցությունը ԴՆԹ-ի լուծույթների հիդրոդինամիկական և սպեկտրալ հատկությունների վրա: Ստացված արդյունքները համեմատվել են մեզո-տետրա-(3N-ալլիլպիրիդիլ) պորֆիրինի (H2TAlPyP4) հետ նախկինում իրականացված նմանատիպ հետազոտությունների արդյունքների հետ: Методами вискозиметрии и спектрофотометрии изучено влияние водорастворимого катионного мезо-тетра-(4N-аллилпиридил) порфирина (H2TAlPyP4) и его комплексов с Cu-, Co- и Zn- на гидродинамическое и спектральное поведение растворов ДНК. Полученные результаты сравнивались с результатами ранее проведенных аналогичных исследований мезо-тетра-(3N-аллилпиридил) порфирина (H2TAlPyP3).
Keywords: Biology; Molecular Biology; Biophysics